Optimization of Thermal Comfort Through Analysis of Passive Design Strategies in Memarong Nok and Memarong Mak Traditional Buildings - Helfa Rahmadyani; Muhammad Fahri (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2026)
The issues of global warming and rising environmental temperatures require a building design approach that can optimize thermal comfort without relying on active cooling systems. Vernacular architecture offers passive design principles based on local wisdom that are adaptive to the climate. This study aims to analyze the application of passive design strategies in the Memarong Nok and Memarong Mak Traditional Buildings in the Gebong Memarong Traditional Village, Mapur Village, Bangka Regency, as a basis for the development of sustainable vernacular architecture. This study employs a mixed-method approach integrating qualitative and quantitative strategies. Qualitative data were obtained through field observations to understand the spatial characteristics and passive design strategies of the building, while quantitative data were collected through on-site measurements of air temperature, relative humidity, wind speed, and solar radiation during peak daytime heat conditions. Thermal comfort analysis was conducted using the adaptive thermal comfort model based on ASHRAE Standard 55 and supported by Thermal Humidity Index (THI) calculations to quantitatively assess the building’s environmental performance. The results of the study show that both buildings are able to achieve thermal comfort conditions at outside temperatures of up to 32°C, with Memarong Nok in the comfortable category (THI 24.0°C) and Memarong Mak in the moderately comfortable category (THI 24.8°C). However, at more extreme outside temperatures, the thermal performance of the buildings declines. These findings confirm that passive design elements such as natural ventilation, the use of lightweight natural materials, building orientation, roof shape, and overhangs play a significant role in controlling heat and humidity. This study concludes that passive design principles based on local wisdom are still relevant and have the potential to be adapted as a sustainable building design strategy that is responsive to today's tropical climate.